Study on sediment discharge in the Marina Bay catchment - Tan, Michelle Mixue. (2009)
This report is a study of the sedimentation effects taking place inside the Marina Bay Catchment. Completed in 2008, it is the latest and largest addition to the reservoirs in Singapore. The catchment holds freshwater inflow from 5 rivers, and is connected to the open sea on the other end, forming an estuary system due to the mixing of freshwater and seawater in the process. The concern of this study stems from the pre-dredging work done to the catchment, and the impact an estuary system brings to both sedimentation and the resulting change to its hydrodynamics. In an effort to obtain a clearer understanding, the MIKE21 software has been utilized for two dimensional modeling and simulation. It was carried out using the Flow Model and Mud Transport Module from the MIKE21 suite. This report also includes the results and data generated from the MIKE21 models. It is followed by an analysis of the results obtained. Salient trends observed during the simulation were also interpreted. As accurate as the available model inputs provided during the modeling process, it can be concluded that the Marina Bay Catchment does not bring about unfavorable effects to the overall environment and poses minor impact on the sedimentation behavior, thus, maintenance dredging will not be required in the near future.